Hospital‐based surveillance of intussusception among infants - Eder Gatti Fernandes; Eyal Leshem; Manish Patel; Brendan Flannery; Alessandra Cristina Guedes Pellini; Maria Amelia Veras; Helena Keico Sato (Brazilian Society of Pediatrics, 2016)
Objective: Intussusception surveillance was initiated after the nationwide introduction of live attenuated monovalent rotavirus vaccine (RV1). The objective is to assess the epidemiology of intussusception and compare the number of cases before and after the introduction of rotavirus vaccine. Methods: Cases of intussusception occurring between March 2006 and January 2008 were identified through a prospective enhanced passive surveillance system established in sentinel state hospitals. Retrospective review of medical records was used to identify cases, which occurred in sentinel hospitals between January 2001 and February 2006. Results: From 2001‐2008, 331 intussusception cases were identified, 59.5% were male, with peak incidence among those 18‐24 weeks of age. Overall < 10% of cases were among infants 6‐14 weeks of age (when the first dose of RV1 is administered). The most frequently observed signs or symptoms of intussusception included vomiting (89.4%), bloody stool (75.5%), and abdominal distention (71.8%). A majority (92.1%) of the case‐patients required surgery for treatment; 31.8% of those who underwent surgery required bowel resection, and 13 (3.9%) died. Among the 21 hospitals that reported cases throughout the entire surveillance period (2001‐2008), the number of intussusception events during 2007 (n = 26) and 2008 (n = 19) was not greater than the average annual number (n = 31, range 24-42) during baseline years 2001‐2005. Conclusions: Although this analysis did not identify an increase in intussusception cases during the two years after RV1 introduction, these results support the need for special epidemiologic methods to assess the potential link between rotavirus vaccine and this very rare adverse event.